2012
DOI: 10.12968/jowc.2012.21.9.421
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of prescribed walking in the management of venous leg ulcers

Abstract: There were no external sources of funding for this study. The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(93 citation statements)
references
References 24 publications
1
84
0
8
Order By: Relevance
“…The only other studies to measure healing as an outcome in an exercise study have reported mixed outcomes with varying endpoints, making direct comparison difficult. Heinen et al reported that their intervention group had less wound days ( P < 0·01), and Meagher et al observed that participants who took more steps at both the baseline and 4‐week assessment healed more quickly than those who took fewer steps ( P = 0·052 and P = 0·008 for baseline and week 4, respectively). In contrast, Jull et al reported no significant differences in ulcer healing parameters (change in area, percentage change in area, number healed at 12 weeks, time to healing).…”
Section: Discussionmentioning
confidence: 99%
“…The only other studies to measure healing as an outcome in an exercise study have reported mixed outcomes with varying endpoints, making direct comparison difficult. Heinen et al reported that their intervention group had less wound days ( P < 0·01), and Meagher et al observed that participants who took more steps at both the baseline and 4‐week assessment healed more quickly than those who took fewer steps ( P = 0·052 and P = 0·008 for baseline and week 4, respectively). In contrast, Jull et al reported no significant differences in ulcer healing parameters (change in area, percentage change in area, number healed at 12 weeks, time to healing).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been considerable attention to promotion of physical activity in Australia, including the development and implementation of the health promotion campaign to encourage adults to walk 10 000 steps per day. Meagher et al recommended adults with VLUs a walking regimen of 10 000 steps per day and indicated that 33% of their sample met this goal. In contrast, O'Brien et al found that only 9% of participants who received a 12‐week exercise intervention with a telephone coaching component and 6% in the usual care group reported an average of 10 000 steps per day.…”
Section: Discussionmentioning
confidence: 88%
“…People aged 65 years and older are recommended to complete 30 minutes of moderate intensity physical activity on most days . Recent research studies indicate that increased levels of physical activity in VLU patients as an adjunct to compression therapy may reverse venous hypertension, decrease wound‐healing time and prevent wound recurrence . However, despite motivation and interest in being physically active, people with VLU report health‐related obstacles, such as pain, increased wound discharge, and weakness related to comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…peripheral arterial disease and coronary artery disease) . In patients with VLUs, supervised calf muscle exercise has been shown to increase calf muscle pump function and improve lower‐limb haemodynamics, as well as mobility and QoL . A recent systematic review suggested further research to determine whether exercise training has an effect on ulcer healing and QoL …”
mentioning
confidence: 99%